PERSEPSI MAHASISWA IAI AL-AZIS ANGKATAN VIII TERHADAP PESAN DAKWAH USTADZ SYAM ELMARUSY BERTEMA IBADAH DALAM KONTEN MEDIA TIKTOK - Putri Adiniyah Shoheh; Sudirman Tebba; Muhammad N. Abdurrazaq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was conducted at the IAI Al-AZIS Campus and on the TikTok platform which is used personally by ustadz Syam, the target is related to the preaching message of Ustadz Syam Elmarusy on the theme of worship in TikTok media content and how students of IAI AL-AZIS class VIII perceive the preaching message of ustadz Syam Elmarusy in TikTok media content. This research method uses a qualitative approach and is descriptive. Data was collected through interviews with IAI Al-AZIS class VIII students to explore their perceptions of the da'wah message conveyed by ustadz Syam in TikTok media content. Apart from that, direct observation of student interactions and reactions when watching the content. The results of the research show that the preaching message with the theme of worship delivered by ustadz Syam Elmarusy on TikTok uses an informative and persuasive approach. ustadz Syam uses an informative approach to explain the content of the da'wah message in the video, as well as a persuasive approach to invite the audience. The message conveyed does not contain any coercive or coercive elements in it. As for students' perceptions of ustadz Syam Elmarusy's preaching message in TikTok media content. Cognitively, this message provides new knowledge that at that time there had been mistakes when working on it so far. Affectively, this message makes them inspired and motivated to do good things. Keywords: Da'wah message, Tiktok Media, Student Perception